Asuhan Kebidanan Komprehensif pada Ny. H di RSUD Kota Makassar - Karamaha, Pinki; Karuniawati, Nia; Sundari, Sundari (Window of Midwifery Journal, 2025)
Continuity of care midwifery care is the provision of continuous midwifery care from pregnancy, childbirth, newborns, the postpartum period, and family planning to reduce maternal and infant mortality. Continuity of care is a comprehensive service that supports women throughout pregnancy, childbirth, postpartum care, and family planning. The philosophy of comprehensive midwifery care holds that pregnancy and birth are physiological and that the welfare of the mother and fetus must be considered through ongoing care. This relates to the role of midwives as professional healthcare workers, which often involves assisting women throughout the reproductive health cycle. The research aimed to gain real-world experience in implementing comprehensive midwifery care using Verney and Soap's seven-step care management model. The results of the assessment were obtained on Mrs "H" aged 32 years GVIPVAI, at the Makassar City Regional Hospital, the pregnancy was normal, the antenatal care examination was carried out six times, the birth was spontaneous without complications, the baby was born spontaneously with a newborn: 2,900 grams, birth body length 51 cm, head circumference: 33cm chest circumference: 31cm, abdominal circumference: 30cm, Apgar/score: 8/10, gender female. Postpartum progressed normally; complaints were still in the normal category, and family planning care was provided regarding contraceptive counseling. The author concludes that, from pregnancy and childbirth through the newborn period and postpartum period, to family planning, everything is normal without any complications.